Using adapted material and its impact on university students’ motivation (2008)
This article reports on the development of research that sought to increase the motivation of a group of students of English at Universidad Nacional de Colombia, in Bogotá, by means of the design and implementation of adapted material that responds to the necessities and profile of the students. The project started through the application of questionnaires completed by students and teachers regarding their perception towards the material they were currently using. Based on the results we obtained, we started with the design and the implementation of the material. During and after the implementation we again asked students to complete questionnaires in order to obtain their perceptions toward the new material. One of the conclusions was that adapting material can positively influence students’ motivation when learning a foreign language. Key words: Materials design, materials evaluation, materials development, materials adaptation, motivation, global material, local material Este artículo trata sobre el desarrollo de una investigación que buscó aumentar la motivación de un grupo de estudiantes de inglés de la Universidad Nacional de Colombia, Sede Bogotá, a través del diseño e implementación de material adaptado que responda a las necesidades y perfiles de los estudiantes. El proyecto comenzó con la aplicación de cuestionarios a estudiantes y docentes en cuanto a su percepción del material que actualmente estaban usando. Con base en los resultados, se comenzó el diseño e implementación del material. Durante y después de la implementación se aplicaron otros cuestionarios a los estudiantes con el fin de obtener sus percepciones acerca del nuevo material. Una de las conclusiones fue que adaptar material puede influenciar positivamente en la motivación de los estudiantes cuando aprenden una lengua extranjera. Palabras clave: Diseño de materiales, evaluación de materiales, desarrollo de materiales, adaptación de materiales, material global, material local